Diploma courses for strengthening the capacities of professionals in digital technologies for the modernization of climate-smart and sustainable agricultural production. - Munoz, Luis Armando; Campuzano, Mauricio; Patiño Martínez, Andrés Alfonso (2025)
In Colombia, professionals in the agricultural sector require ongoing training, especially in digital technologies and tools that allow them to implement digital solutions on a larger scale, with a focus on sustainability in the face of climate change. The Alliance of Bioversity and International Centers for Tropical Agriculture (CIAT), along with its researchers, has partnered with national universities and other private entities to design formal training courses. These courses generate certificates endorsed by the Ministry of Education, enabling professionals who complete these diploma programs to enhance their skills and advance their careers in any organization they may work for, whether private or public. Through these partnerships, nearly 200 agricultural professionals have been trained between 2024 and 2025. Furthermore, the participating universities have strengthened their expertise in these areas and are now able to offer these diploma courses on an ongoing basis.